1998
DOI: 10.1093/emboj/17.7.2008
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Src/p21ras/Erk pathway by progesterone receptor via cross-talk with estrogen receptor

Abstract: The molecular mechanisms by which ovarian hormones stimulate growth of breast tumors are unclear. It has been reported previously that estrogens activate the signal-transducing Src/p21 ras /Erk pathway in human breast cancer cells via an interaction of estrogen receptor (ER) with c-Src. We now show that progestins stimulate human breast cancer T47D cell proliferation and induce a similar rapid and transient activation of the pathway which, surprisingly, is blocked not only by anti-progestins but also by anti-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
488
1
4

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 577 publications
(522 citation statements)
references
References 64 publications
29
488
1
4
Order By: Relevance
“…This is in agreement with reports of ER and PR activating MAP kinase through the Ras-Raf-1-MEK pathway (Migliaccio et al, , 1998. In addition, we have shown for the AR that PI3 kinase and PKC also contribute to the DHT-mediated activation of MAP kinase.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This is in agreement with reports of ER and PR activating MAP kinase through the Ras-Raf-1-MEK pathway (Migliaccio et al, , 1998. In addition, we have shown for the AR that PI3 kinase and PKC also contribute to the DHT-mediated activation of MAP kinase.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, a number of steroid hormones are reported to rapidly and reversibly activate important intermediates in signal transduction pathways known to trigger cell proliferation (Migliaccio et al, , 1998Endoh et al, 1997;Marcinkowska et al, 1997). For example estrogens activate two members in the family of c-srcrelated tyrosine kinases, c-src and c-yes as well as the MAP kinases Erk-1 and -2 (Di .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Western blotting using phospho-specific antibodies indicated that EGF stimulation of T47D cells induces phosphorylation of PR Ser294 at 5-10 min, similar to that induced by R5020 at early time points (15,16). Both agents are known to activate MAPKs within 5-15 minutes (25,26). However, EGF is a stronger activator of MAPK relative to progestins at this time point, and liganded PRs are relatively transient, most likely due to the rapid down-regulation of liganded and Ser294 phosphorylated species (14).…”
Section: Egf Induces Pr Nuclear Association and Pre Bindingmentioning
confidence: 88%